Integrasi Islam Sosialisme dan Paham Komunis dalam Menghadapi Kapitalisme di Padang Panjang (1923-1927) - Friska Syafitri; Muhamad Jono (HEURISTIK: Jurnal Pendidikan Sejarah, 2021)
The results of this study present a historical study of the involvement of a teacher with the title Datuak and several teachers in one of the pesantren, the center of Islamic modernists in Minangkabau and Islamic communists in the early 20th century. As a religious elite, teachers play an important role in the formation of the lives of their students, including in politics. Around 1923-1927, the teachers took a central role in the expansion of the communist seeds to counter colonial government policies, in addition to being prominent pesantren and Datuak teachers. Related to the theme of this study, the interesting thing is that the students and some pesantren teachers joined the PKI, which expressly had a cross-party ideology. This study focuses on how the process and forms of integration of socialism and Islam with communist understanding in the face of capitalism in Padang Panjang. In this case, the author found strong evidence that for some teachers and Datuak at the time, the PKI's values and vision were not contrary to Islamic tradition.